An Inhibitory Effect of Dryocrassin ABBA on Staphylococcus aureus vWbp That Protects Mice From Pneumonia - Li, Bangbang; Jin, Yingli; Xiang, Hua; Mu, Dan; Yang, Panpan; Li, Xianmei; Zhong, Ling; Cao, Junjie; Xu, Dan; Gong, Qian; Wang, Tiedong; Wang, Lin; et al. (Frontiers in Microbiology, 2019)
Von Willebrand factor-binding protein (vWbp), secreted by Staphylococcus aureus (S. aureus), can activate host prothrombin, convert fibrinogen to fibrin clots, induce blood clotting, and contribute to pathophysiology of S. aureus-related diseases, including infective endocarditis, staphylococcal sepsis and pneumonia. Therefore, vWbp is an promising drug target in the treatment of S. aureus-related infections. Here, we report that dryocrassin ABBA (ABBA), a natural compound derived from Dryopteris crassirhizoma, can significantly inhibit the coagulase activity of vWbp in vitro by directly interacting with vWbp without killing the bacteria or inhibiting the expression of the vWbp. Using molecular dynamics simulations, we demonstrate that ABBA binds to the ‘central cavity’ in the elbow of vWbp by interacting with Arg-70, His-71, Ala-72, Gly-73, Tyr-74, Glu-75, Tyr-83 and Gln-87 in vWbp, thus interfering with the binding of vWbp to prothrombin. Furthermore, in vivo studies demonstrated that ABBA can attenuate injury and inflammation of mouse lung tissues caused by S. aureus and increase survival of mice. Together these findings indicate that ABBA is a promising lead drug for the treatment of S. aureus-related infections. This is the first report of potential inhibitor which inhibit the coagulase activity of vWbp by directly interacting with vWbp.